Pediatric Urinary Stone Disease: A 10-Year Single-Center Experience from Türkiye - Utku Dönger; Caner İncekaş; Kaan Savaş Gülleroğlu; Esra Baskın (Turkish Archives of Pediatrics)
Objective: Urinary stone disease (USD) is characterized by stone formation in the urinary system with an approximate prevalence of 5%-10% in children. In thisr study, the authors investigated the metabolic abnormalities that play a role in stone formation in pediatric patients with USD admitted to the authors’ pediatric nephrology clinic during the last 10 years, the demographic characteristics of the patients, and the presenting symptoms.